2016
DOI: 10.1051/0004-6361/201527863
|View full text |Cite
|
Sign up to set email alerts
|

An M-dwarf star in the transition disk of Herbig HD 142527

Abstract: Aims. HD 42527A is one of the most studied Herbig Ae/Be stars with a transitional disk, as it has the largest imaged gap in any protoplanetary disk: the gas is cleared from 30 to 90 AU. The HD 142527 system is also unique in that it has a stellar companion with a small mass compared to the mass of the primary star. This factor of ≈20 in mass ratio between the two objects makes this binary system different from any other YSO. The HD 142527 system could therefore provide a valuable test bed for understanding the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
121
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(141 citation statements)
references
References 33 publications
(60 reference statements)
15
121
5
Order By: Relevance
“…Whereas a massive planet exterior to the arms can generate the observed two-arm spirals, a stellar companion closer than ∼5″ could produce a similar spiral structure in a disk with a typical size of ∼1-2″ (e.g., as in the HD 100453 disk; Wagner et al 2015;Dong et al 2016c;Wagner et al 2018). The companion to HD142527, which is located well within the gap in the disk, is commonly interpreted as having too low a mass (0.13 M e ; Lacour et al 2016) and eccentricity to generate the observed spiral arms, so this object is included in our sample (although see Price et al 2018). Lastly, we removed HD141569 from the sample, because its low dust mass (on the order of 1 M ⊕ or less; Flaherty et al 2016;White et al 2016) makes the system prone to radiation pressure and photoelectric instability, which can also produce spiral arm structures (e.g., Richert et al 2018b).…”
Section: Disk Imaging Samplementioning
confidence: 99%
“…Whereas a massive planet exterior to the arms can generate the observed two-arm spirals, a stellar companion closer than ∼5″ could produce a similar spiral structure in a disk with a typical size of ∼1-2″ (e.g., as in the HD 100453 disk; Wagner et al 2015;Dong et al 2016c;Wagner et al 2018). The companion to HD142527, which is located well within the gap in the disk, is commonly interpreted as having too low a mass (0.13 M e ; Lacour et al 2016) and eccentricity to generate the observed spiral arms, so this object is included in our sample (although see Price et al 2018). Lastly, we removed HD141569 from the sample, because its low dust mass (on the order of 1 M ⊕ or less; Flaherty et al 2016;White et al 2016) makes the system prone to radiation pressure and photoelectric instability, which can also produce spiral arm structures (e.g., Richert et al 2018b).…”
Section: Disk Imaging Samplementioning
confidence: 99%
“…Recent simulations by Lacour et al (2016) have shown that the companion is probably orbiting on the inner disk plane, not coplanar with the outer disk, with an eccentricity of about 0.6 not sufficient to explain the dust cavity size. Furthermore, this interaction should lead to the formation of a gas density maximum very close to the cavity edge, i.e., between 40-60 AU.…”
Section: Origin Of the Central Cavitymentioning
confidence: 97%
“…The primary star is an Herbig FeIIIe star with a mass of 2.4 M (Verhoeff et al 2011) which is accreting material at the rate of about 10 −7 M yr −1 (Garcia Lopez et al 2006;Mendigutía et al 2014). The secondary star has a mass between 0.1-0.3 M , an orbital radius between 15-20 AU, and a mass accretion rate of ∼ 6 × 10 −10 M yr −1 (Biller et al 2012;Close et al 2014;Lacour et al 2016). The binary system is at the center of a large elliptical dust cavity of about 120 AU in radius and of an asymmetric disk with a dense dust crescent on the north side (Ohashi 2008;.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison with LkCa 15b is found in the next section. The L Hα of HD 142527 B (Close et al 2014), which is a low-mass M dwarf (Lacour et al 2016), is also shown for comparison.…”
Section: Accretion Shock and Internal Luminositiesmentioning
confidence: 99%